PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 016 PULAU RAMBAI KECAMATAN KAMPAR TIMUR - ', Mariana; Marhadi, Hendri; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the fact that low student learning outcomes IPS. It can be seen from the IPS students with the average - average of 60. The percentage of students who achieve KKM only 45% of the 20 students, so the number of students who completed only 9 people. The purpose of this research is to improve student learning outcomes IPS Class IV Elementary School 016 East Kampar District Pulau Rambai with the implementation of cooperative learning model type STAD. Activities teachers during the learning process by using STAD cooperative learning experience penigkatan. In cycle 1 to the first meeting with the average - average 47% of the category